2023
DOI: 10.1186/s12913-023-09556-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical activity on healthcare costs: a systematic review

Abstract: Background This systematic review aims to describe the relation between physical inactivity and healthcare costs, by taking into account healthcare costs of physical-inactivity-related diseases (common practice), including physical-activity-related injuries (new) and costs in life-years gained due to avoiding diseases (new), whenever available. Moreover, the association between physical inactivity and healthcare costs may both be negatively and positively impacted by increased physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Higher levels of physical activity during hospitalisation are associated with faster recovery [ 2 – 4 ], shorter length of hospital stay [ 2 , 3 ], lower risk of early readmission [ 5 ], and lower rates of adverse events [ 4 ]. Low levels of lifestyle physical activity, are also correlated with increased rates of hospitalisation [ 6 , 7 ], and higher overall healthcare costs [ 8 ]. Despite the overwhelming evidence supporting the benefits of physical activity for clinical populations [ 9 ], it remains under-promoted and under-prioritised in healthcare settings [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of physical activity during hospitalisation are associated with faster recovery [ 2 – 4 ], shorter length of hospital stay [ 2 , 3 ], lower risk of early readmission [ 5 ], and lower rates of adverse events [ 4 ]. Low levels of lifestyle physical activity, are also correlated with increased rates of hospitalisation [ 6 , 7 ], and higher overall healthcare costs [ 8 ]. Despite the overwhelming evidence supporting the benefits of physical activity for clinical populations [ 9 ], it remains under-promoted and under-prioritised in healthcare settings [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this domain, walking and cycling are important manifestations of physical exercise among adults 7 , being potential behaviors to prevent chronic diseases and hence mitigate health costs. However, in developing nations, not much is known about the economic burden of walking and cycling 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most data describing the association of walking and cycling with economic aspects are based on cross-sectional surveys and carried out in developed settings 8 , 9 , leading to technical questions about its application in developing nations. Such issue seems even more relevant in the Brazilian scenario, in which healthcare assistance is financed by public fundings (at all levels of complexity).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease, a progressive brain disorder that leads to a gradual loss of memory/thinking/language skills, was reported to be considerably prevented by long-term regular exercise [ 5 , 6 ]. Recently, an economic cost analysis in the UK on exercise intervention for patients with chronic obstructive pulmonary disease showcased that regular physical activity could save patients up to £200 monthly by reducing mortality [ 7 ] and hospitalization rates, while exercise was reported to reduce the health care costs by 9.0% to 26.6% around the world [ 8 ]. In the context of cancer treatment, our team recently revealed that exercise can metamorphose the immunological microenvironment of non-small-cell lung cancer, transitioning it from “cold” to “hot”, which suggested that exercise increases the number of immune cells such as CD8 + T cells, M1 macrophages, etc.…”
mentioning
confidence: 99%